Expression of protein phosphatase 4 in different tissues under hypoxia - Yanyan Ma; Jing Hou; Dengliang Huang; Yaogang Zhang; Zhe Liu; Meiyuan Tian (Indian Journal of Pathology and Microbiology)
Relevant research data shows that there is a certain degree of energy metabolism imbalance in highland residents. Protein phosphatase 4 (PP4) has been found as a new factor in the regulation of sugar and lipid metabolism. Here, we investigate the differential expression of PP4 at a simulated altitude of 4,500 m in the heart, lung, and brain tissues of rats. A hypoxic plateau rat model was established using an animal decompression chamber. A blood routine test was performed by an animal blood cell analyzer on rats cultured for different hypoxia periods at 4,500 m above sea level. Quantitative polymerase chain reaction (qPCR) and western blot were used to detect the changes of protein phosphatase 4 catalytic subunit (PP4C) gene and protein in heart, lung, and brain tissues. The PP4C gene with the highest expression level found in rats slowly entering the high altitude area (20 m-2200 m-7 d-4500 m-3 d) was about twice as high as the low elevation group (20 m above sea level). The simulated high-altitude hypoxia induced an increase of PP4C expression level in all tissues, and the expression in the lung tissue was twice as expressed as heart and brain tissue at high altitude (P < 0.05). These results suggest that the PP4 phosphatase complex is ubiquitously expressed in rat tissues and likely involved in adaptation to or disease associated with high-altitude hypoxia.